If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(1 + 4n) = -279 (1 * 9 + 4n * 9) = -279 (9 + 36n) = -279 Solving 9 + 36n = -279 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 36n = -279 + -9 Combine like terms: 9 + -9 = 0 0 + 36n = -279 + -9 36n = -279 + -9 Combine like terms: -279 + -9 = -288 36n = -288 Divide each side by '36'. n = -8 Simplifying n = -8
| 4-11b=15 | | 1/z=12/10z-8 | | g-9/9=4/9 | | 3y-5d=5d-4 | | 13+3s=-47 | | 6r+27=30 | | (x-2)(3x-12)=0 | | k-8/2=12 | | 13/8m=1/2 | | -5/2*=34 | | -2m/3=-12 | | 5(x+20)=3x+180 | | 3a-8=-6+8 | | 22=6c | | 8(-2x-4)+13=-52 | | x^4+4x^3 -x^2 +16x-20=0 | | 3a+9=4a-1 | | x^3-2x^2+5x-2=0 | | X-2/5=3/x | | 7+0.6y=19 | | 8x=26-50 | | 2x+16=130 | | 89-2x=6x+8 | | 3x+5-9=9 | | 4.2x=-4(0.62-1.2) | | 9x+40=3x+4 | | d-7=524 | | t/7.5=4 | | t/7.5-4 | | -21=n+3-5n | | 3x^2+19x-51=0 | | 1.3x+2.4=7.5 |